Direct Growth of Vertically Orientated Nanocavity Arrays for Plasmonic Color Generation. (21st June 2020) - Hu, Haibo; Gao, Wenjie; Zang, Rui; Gao, Junhua; Tang, Shiwei; Li, Xiaoyun; Liang, Lingyan; Zhang, Hongliang; Cao, Hongtao
Abstract: Plasmonic structural colors, arising from resonance interactions between photons and metallic nanostructures, have been developed rapidly for high‐end applications. However, common structural color materials and fabrication methods usually have open plasmonic nanostructures and limited scalability, respectively. Here, a new scheme based on Ag nanowire arrays/SiO2 composite metamaterial films with subwavelength enclosed nanostructures involved that combine a dielectric gap layer and a metal mirror is presented. The whole stacked structure can be simply prepared only via magnetron sputtering without any other procedures. Specifically, by changing deposition parameters, the geometry size and sub‐10 nm periodic parameters of the structure unit cell array can be finely tuned in a controllable and reproducible way. By experiments and simulations, it is demonstrated how interwire coupled plasmonic transverse modes in vertically orientated nanocavity arrays control multiple nanocavity standing‐wave resonances at visible wavelengths, generating three primary colors‐included bright and saturated colors across a wide gamut. Large‐area and uniform structural colors, whether on rigid or flexible substrates, show angle‐insensitive and air‐stable features. In a wider perspective, this work suggests that the material scheme and fabrication advances represent a robust platform for plasmonic color designing, theory exploring, and large‐scale manufacturing. Abstract : It is still a great challenge to achieve large‐scale structural colors with closed plasmonic nanostructures. Here, a nanowire array‐based plasmonic coloring structure is proposed, demonstrating vivid colors across a wide gamut. The entire stacked structure can be directly deposited only via magnetron sputtering without any other procedures.